2020
DOI: 10.1111/padr.12344
|View full text |Cite
|
Sign up to set email alerts
|

International Migration and City Growth in the Global South: An Analysis of IPUMS Data for Seven Countries, 1992–2013

Abstract: Evidence on the demographic components of city growth in the global South is scarce, and the role played by international migration is neglected. We analyze the importance of recent international migration in cities, compare it with that of internal movements, and evaluate the growth contribution across national contexts and the urban hierarchy. Combining individual-level census data and geographic master files of metropolitan areas with indirect demographic estimation techniques, we cover 377 cities in seven … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…Yet, without enough evidence across countries of rural/urban origin and destination of international migrants, it is not possible to fully understand the role of international flows in the urban transition. Nevertheless, based on evidence from low‐ and middle‐income countries which suggests that as cities grow, net international migration substitutes losses from net internal migration in large cities, we expect that at higher levels of urbanization, international migration plays a larger role (Lerch 2020). Broadly, if it were possible to include international migration, we would expect that the role of migration‐reclassification would be lower.…”
Section: Methodsmentioning
confidence: 98%
“…Yet, without enough evidence across countries of rural/urban origin and destination of international migrants, it is not possible to fully understand the role of international flows in the urban transition. Nevertheless, based on evidence from low‐ and middle‐income countries which suggests that as cities grow, net international migration substitutes losses from net internal migration in large cities, we expect that at higher levels of urbanization, international migration plays a larger role (Lerch 2020). Broadly, if it were possible to include international migration, we would expect that the role of migration‐reclassification would be lower.…”
Section: Methodsmentioning
confidence: 98%
“…Moreover, the traditional focus on net migration (i.e., the difference between the number of immigrants and the number of outmigrants) has hidden the relevance of migratory flows for demography (Rogers 1990 ). While the relevance of migratory flows in shaping population change has been documented at the level of cities (Lerch 2020 ), we have shown that it is also relevant for many societies and that this relevance might change over time.…”
Section: Discussionmentioning
confidence: 57%
“…At the national level, some statistical offices produce estimates of population flows that include immigration and emigration, also on an annual basis. For our case studies, we use official estimates provided by the national statistical institutes of Germany (DESTATIS-Federal Statistical Office, data between 1990 and2020) and Italy (ISTAT-Italian National Institute of Statistics, data between 1916 and 2020) (note that for both Germany and Italy, the 2020 data we use are still considered provisional).…”
Section: The Speed Of Population Change: Data and Methodsmentioning
confidence: 99%
“…This, coupled with a failure of statistical and census bodies to capture cyclical migration, explains, in Kundu's view, India's low urbanisation rates. In contrast to other Southern cities where migration typically accounts for higher percentages of urban growth, its contribution in Indian cities has hovered around 20% (Bhagat, 2018;Lerch, 2020). Thus rural-to-urban reclassification, that is, territorial transformation, takes on a greater role in accounting for urbanisation.…”
Section: Urbanisation and Spatial Transformationsmentioning
confidence: 99%